2011
DOI: 10.1111/j.1553-2712.2011.01082.x
|View full text |Cite
|
Sign up to set email alerts
|

An Empirical Assessment of Boarding and Quality of Care: Delays in Care Among Chest Pain, Pneumonia, and Cellulitis Patients

Abstract: Background: As hospital crowding has increased, more patients have ended up boarding in the emergency department (ED) awaiting their inpatient beds. To the best of our knowledge, no study has compared the quality of care of boarded and nonboarded patients.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
36
0

Year Published

2012
2012
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 46 publications
(36 citation statements)
references
References 44 publications
0
36
0
Order By: Relevance
“…However, as there is a paucity of literature on bedspacing itself, we feel that relevant inferences may be drawn from the Emergency Department (ED) overcrowding literature. Patients who remain in the ED after admission, but do not yet have an inpatient bed, have been referred to as “boarders.” Evidence suggests that boarders have increased lengths of stay, delays in home medication administration, and overall delays in medical care [5]-[9]. One study demonstrated an association with increased in-hospital mortality rates [10].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…However, as there is a paucity of literature on bedspacing itself, we feel that relevant inferences may be drawn from the Emergency Department (ED) overcrowding literature. Patients who remain in the ED after admission, but do not yet have an inpatient bed, have been referred to as “boarders.” Evidence suggests that boarders have increased lengths of stay, delays in home medication administration, and overall delays in medical care [5]-[9]. One study demonstrated an association with increased in-hospital mortality rates [10].…”
Section: Discussionmentioning
confidence: 99%
“…While bedspacing is a routine occurrence in many hospitals, it is unclear whether this practice compromises patient care. Evidence from similar patient populations who are physically separated from the medical team has shown that clinician-patient barriers can result in poorer quality of care [5][10]. As care needs may differ between GIM and non-GIM patients, non-GIM “host” services may have less experience with GIM patients, and ultimately, bedspaced patients may have compromised quality of care (for example, with poorer nursing adherence to quality measures) [11], [12].…”
Section: Introductionmentioning
confidence: 99%
“…6 Some studies have demonstrated an association between length of emergency department boarding of patients and mortality, increased overall length of stay, 14 medication delays, and adverse events. 15,16 …”
Section: Discussionmentioning
confidence: 99%
“…These findings are consistent with previous studies that found no association between hallway boarding and medication delays or adverse events. [14,18] We acknowledge that the eligibility criteria for inpatient hallway admission may introduce some selection bias. However, these criteria were developed and implemented institution-wide as temporary hallway beds did not have infrastructure capabilities to support isolation, telemetry or high flow oxygen.…”
Section: Discussionmentioning
confidence: 99%